금융위기에 대응한 확장적 재정정책의 효과성 분석 - 김성태 (12711, 2012)
This study outlines measures related to fiscal policies aimed at responding to the financial crisis according to the timing of commencement and then examines impacts of expansionary fiscal policies on macro variables so as to extract policy implications.